Embedding Prefetching of Audio Content in ARM Processors - Spetz Rasmussen, Anders (My University, 2017)
This paper describes the design and implementation an audio amplifier host module. The hardware developed served as a physical interface between the amplifier and an ARM equipped evaluation board capable of running the Linux kernel. Both hardware and software development was carried out at amplifier manufacturer Lab.gruppen facilities according to specified technical requirements. The project resulted in a functioning embedded audio player prototype. More specifically, the project resulted in the necessary underlying hardware and firmware that is intended to serve as a platform for further development of the amplifier host module.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science